2019
DOI: 10.1002/jbmr.3695
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a Brd4 Mutation Represent a New Model of Nephrocalcinosis

Abstract: Nephrolithiasis (NL) and nephrocalcinosis (NC), which comprise renal calcification of the collecting system and parenchyma, respectively, have a multifactorial etiology with environmental and genetic determinants and affect ∼10% of adults by age 70 years. Studies of families with hereditary NL and NC have identified >30 causative genes that have increased our understanding of extracellular calcium homeostasis and renal tubular transport of calcium. However, these account for <20% of the likely genes that are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…1G and H ). Bone metabolism was assessed by whole body dual-energy X-ray absorptiometry (DXA), and by measurement of the pro collagen type 1 N-terminal pro-peptide (P1NP) and C-terminal cross-linking telopeptide of type 1 collagen (CTX-1) bone turnover markers, as reported ( 18 , 19 ). Bone mineral content (BMC) corrected for body weight, BMD, and bone turnover in male and female Ap2s1 +/L15 mice were not significantly different to those observed in age- and sex-matched WT mice ( Table 2 and Supplementary Material, Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1G and H ). Bone metabolism was assessed by whole body dual-energy X-ray absorptiometry (DXA), and by measurement of the pro collagen type 1 N-terminal pro-peptide (P1NP) and C-terminal cross-linking telopeptide of type 1 collagen (CTX-1) bone turnover markers, as reported ( 18 , 19 ). Bone mineral content (BMC) corrected for body weight, BMD, and bone turnover in male and female Ap2s1 +/L15 mice were not significantly different to those observed in age- and sex-matched WT mice ( Table 2 and Supplementary Material, Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…C-terminal cross-linking telopeptide of type 1 collagen (CTX-1) was measured using a mouse-specific ELISA (Biorbyt Ltd). Procollagen type 1 N-terminal propeptide (P1NP) was measured by an enzyme immunoassay (EIA) (Immunodiagnostic Systems) ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Phenotype of mice harboring the Ap2s1 mutation, p.Arg15Leu. Adult Ap2s1 +/L15 mice, aged [12][13][14][15][16][17][18][19][20][21][22] weeks, showed no gross morphological abnormalities, although male Ap2s1 +/L15 mice had a significantly reduced body weight when compared to age-matched WT male litter-mates, whereas female Ap2s1 +/L15 mice had a normal body weight (Table 2). Activities such as eating, drinking, grooming, moving and interacting with cage-mates were observed to be similar between Ap2s1 +/L15…”
Section: Resultsmentioning
confidence: 99%
“…Urine biochemical analysis showed that female Ap2s1 +/L15 mice had significantly reduced 24 hour urine calcium excretion, whereas male Ap2s1 +/L15 mice showed a significantly increased fractional excretion of phosphate, but no alterations of urine calcium excretion when compared to WT mice (Table 2, Figure 2G-H). Bone metabolism was assessed by whole body dual-energy X-ray absorptiometry (DXA), and by measurement of the pro-collagen type 1 N-terminal pro-peptide (P1NP) bone turnover marker, as reported (18,19). Bone mineral content (BMC) corrected for body weight, BMD, and bone turnover in male and female Ap2s1 +/L15 mice were not significantly different to those observed in sexmatched WT mice (Table 2 and Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation